Extended Legendre Wavelet Method for Solving Fractional Order Time Hyperbolic Partial Differential Equation - Gupta, Sandipan; Thakur, Bharti (International journal of applied and computational mathematics, 2023)
An efficient numerical technique is developed for solving fractional order time hyperbolic partial differential equations by using the extended Legendre wavelet method. The fractional integral of extended Legendre wavelet in Riemann–Liouville sense is obtained by using Laplace transformation. The proposed scheme is established to compute an approximate solution and also to achieve a high degree of accuracy with a low computational cost. The solution obtained by the Extended Legendre wavelet method and standard Legendre wavelet method has been compared with their exact solution. Moreover, the convergence behavior and error analysis of the proposed method is studied through several examples.